Experimental Investigation on Seismic Performance of Precast Column-Foundation Connection using Combined Anchor and Pocket System - Propika, Jaka; Pudjisuryadi, Pamuda; Chandra, Jimmy (Institute of Research and Community Outreach - Petra Christian University, 2026)
Connections between precast concrete elements play a crucial role in ensuring structural integrity and facilitating effective force transfer. Among various connection types, the column–foundation connection is the most critical component, as it is designed to resist the combined effects of axial load, bending moment, and shear force. In this study, the pocket connection was modified with anchored reinforcement (BPC) to improve seismic performance. An experimental program was conducted on three specimens: a monolithic cast-in-place connection (MC) as the control, a conventional pocket connection (PC), and the modified pocket connection (BPC). Each specimen was subjected to combined axial and cyclic loading to evaluate the seismic performance of the column–foundation connection. The results showed that the MC specimen demonstrated the best performance, while the PC specimen, although meeting the ACI 374.1-05 acceptance criteria, failed to achieve the required probable moment capacity. The BPC specimen demonstrated improvement in seismic performance compared to the PC and was considered suitable for use in precast structural systems designed for seismic area.